Peran Kepuasan Kerja Memediasi Pengaruh Stres Kerja Terhadap Turnover Intention (Studi pada Cv. Bali Harmoni Bali Zoo) - Aksa Ardindha; I Gede Riana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Turnover intention refers to the desire or intention of employees to voluntarily resign or move to another workplace according to their wishes. The purpose of this study is to study how job satisfaction functions as a mediator in the relationship between job stress and the desire to resign of employees of CV. Bali Harmoni Bali Zoo. This study involved 58 employee respondents and used a survey method through questionnaires and interviews, and was analyzed using inferential statistical techniques in the form of path analysis. The results of the study indicate that job stress affects the desire to move jobs positively and significantly. In addition, Job stress has a negative and significant effect on job satisfaction, and job satisfaction has a negative and significant effect on turnover intention. Thus, the job satisfaction variable is proven to be able to mediate the effect of job stress on turnover intention.